Chinese Immigrants in Peru - Rodríguez, Humberto (1984)
This work is an attempt to facilitate to historians and social scientists –or any other person- everything that is so far published about Chinese in Peru, as well as to signalize the sources to look in order to delve in the different topics of historical research about Chinese immigrants.